Case report: A pediatric case of MPO-ANCA-associated granulomatosis with polyangiitis superimposed on post-streptococcal acute glomerulonephritis - Kuang, Qianhuining; He, Xu; Jia, Lili; Zhang, Zhiqiang; Gui, Chunhong; Gao, Chunlin; Xia, Zhengkun (Frontiers in Pediatrics, 2023)
An eight-year-old girl with vomiting, gross hematuria and progressive renal dysfunction was admitted. Renal biopsy revealed endocapillary proliferative glomerulopathy and crescent formation. Immunofluorescence staining revealed diffuse granular deposits of IgG and C3. Post-streptococcal acute glomerulonephritis (PSAGN) was suspected based on the elevated anti-streptolysin O levels, decreased serum C3 concentrations and histological findings. The myeloperoxidase antineutrophil cytoplasmic antibody (MPO-ANCA) test was positive, and she developed palisaded neutrophilic and granulomatous dermatitis (PNGD), orbital and sinus granulomatous neoplasms gradually, along with intermittent nose pain, headache, and orbital pain. Finally, she was diagnosed with rare MPO-ANCA associated granulomatosis with polyangiitis (GPA) superimposed on PSAGN. The patient was treated with aggressive renal replacement therapy, methylprednisolone pulse therapy and intravenous pulse cyclophosphamide; her renal function normalized, and the symptoms of pain improved.